Neuroscience : from the molecular to the cognitive - Bloom, Floyd E. (Progress in brain research, 1994)
This hundredth volume is a commemorative milestone in the prestigious Progress in Brain Research series. Accordingly, authors were invited to write on any topic, given that their choice represented the topic most near and dear to their own efforts over a significant period of the recent past, and to which they would likely continue to be devoted in the future. In that sense, this volume does not represent a scientific meeting, but rather an overview sample of problems and methodologies that epitomize brain research broadly at this special moment in the maturation of the field. The chapters comprising this volume assort themselves readily into five or six established categories of topics: developmental brain research, molecular brain research, integrative brain research, neuroplasticity, and neuro-psychiatric conditions. This volume reports through a sample of recognized leaders in the neuroscientific community at a significant instant in the history and evolution of the field.